A candidate strategy to achieve high initial Coulombic efficiency and long cycle life of Si anode materials: exterior carbon coating on porous Si microparticles. (September 2017) - Li, Bo; Xiao, Zhujun; Zai, Jiantao; Chen, Ming; Wang, Honghui; Liu, Xuejiao; Li, Guan; Qian, Xuefeng
Abstract: Cycling stability of Si anode materials has been significantly improved, but there was rare progress on its initial Coulombic efficiency, which is an essential factor for the overall capacity and energy density of full batteries. The challenge is to fabricate porous Si/C materials with small surface area by depositing carbon as less as possible and maintaining the interior porous structure of Si to achieve high initial Coulombic efficiency and good cycling stability at the same time. Herein, porous Si microparticles with pore size of ∼2.8 nm were successfully prepared. The surface area could be significantly reduced from 235.6 m 2 g −1 to 32.4 m 2 g −1 by coating carbon as low as 5.8 wt % because the narrow external openings of pores on Si microparticle were easily closed to leave the interior pores unfilled. As a result, the initial Coulombic efficiency of the as-prepared Si/C microparticles reached to 87.5% with a high reversible capability of 2242 mAh g −1 at 0.4 A g −1 after 100 cycles and long-term cycling stability (886 mAh g −1 at 2 A g −1 after 500 cycles). Graphical abstract: Highlights: Exterior carbon-coated porous Si/C microparticles were rational designed and prepared. Reduced surface area with low content of carbon (5.8 wt %) and unfilled interior pores. The initial Coulombic efficiency of the as-prepared Si/C microparticles reached to 87.5%.